Guatemala : Fourth Review Under the Stand-By Arrangement; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Guatemala. (IMF Staff Country Reports; Country Report ;, 2010)
The natural disasters that hit the country recently caused human losses and had a negative impact on the economy; however, they did not deviate the economic recovery path. Currently, growth in exports and imports is accelerating, remittances are recovering, and international reserves are well above end-2009 levels. The authorities have recently adopted regulations on liquidity and foreign currency credit risk management and have made further progress toward full provisioning of nonperforming loans. Finally, the IMF-supported program has also contributed to the achievement of their economic program goals.